PENGEMBANGAN INSTRUMEN ANGKET PERSEPSI MAHASISWA PENDIDIKAN BIOLOGI UNIVERSITAS TANJUNGPURA TERHADAP PELAKSANAAN KEGIATAN PENDIDIKAN KARAKTER - Sari, Natalia Wulan; Mardiyyaningsih, Asriah Nurdini; Wahyuni, Eko Sri (Universitas Tanjungpura, 2025)
This research aims to develop a questionnaire instrument to assess biology education students' perceptions of the implementation of Pancasila-based character education activities at Tanjungpura University in supporting the formation of scientist characters that biology teacher candidates must possess, meeting the criteria of validity and reliability. the research and development stages include:1) Potential and problems, 2) Data collection, 3) Product design, 4) Design validation, 5) Design revision, 6) Product trial, 7) Product revision, 1 8) Usage trial. The statements in the perception questionnaire for biology education students regarding the implementation of character education at Tanjungpura University consist of 52 statements. The questionnaire trial was conducted on 30 non-participant biology education students from the 2020 cohort who had participated in character education activities at Tanjungpura University. Based on the validation and reliability results, 29 questionnaire statements were deemed suitable, with the highest validation score of 0.530 and the lowest of 0.367, both greater than the r-table value (0.361). The reliability value is 0.8755, categorized as very high.